Product management in practice : a real-world guide to the key connective role of the 21st century - LeMay, Matthew (Ascent Audio, 2021)
Product management has become a critical connective role for modern organizations, from small technology startups to global corporate enterprises. And yet the day-to-day work of product management remains largely misunderstood. In theory, product management is about building products that people love. The real-world practice of product management is often about difficult conversations, practical compromises, and hard-won incremental gains. In this book, author Matt LeMay focuses on the CORE connective skills-- communication, organization, research, execution--that can build a successful product management practice across industries, organizations, teams, and toolsets. For current and aspiring product managers, this book explores: On-the-ground tactics for facilitating collaboration and communication How to talk to users and work with executives The importance of setting clear and actionable goals Using roadmaps to connect and align your team A values-first approach to implementing Agile practices Common behavioral traps that turn good product managers bad.